Experimental investigations in vertical vibration damping of agricultural aggregate of block-modular type - Bulgakov, Volodymyr; Булгаков, Володимир Михайлович; Булгаков, Владимир Михайлович; Kuvachov, Volodymyr; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Ivanovs, S. (My University, 2021)
Under conditions of real operation of block-modular aggregates continuous oscillations of external disturbances lead to a decrease in their technical and operational indicators and an increase in specific fuel consumption per unit of the work performed. Evaluation of the performance indicators of a block-modular agricultural aggregate, based on the MTZ-82 serial tractor with a technological module was carried out on the basis of laboratory-field research on ploughing cereal stubble. These investigations were performed by means of a strain gauge measuring complex that recorded signals on a PC, using an analogue-to-digital converter. The results obtained were processed in the Matlab program. Creation of a rational elastic-damping connection between the tractor and the technological module allows obtaining the desired amplitude-frequency and correlation-spectral characteristics of vertical oscillations of a modular agricultural aggregate, reducing the dispersion of the torque oscillations on the tractor power take-off shaft by 10 times. An elastic-damping connection between the tractor and the technological module with a drag coefficient of 1.65 kN·s·m-1 on ploughing has made it possible to reduce by 3-4 times the dispersion of vertical vibrations of the block-modular aggregate, to increase its performance by 6%.
Keywords: block-modular aggregate; damping; vibration; oscillations